P457 Transcatheter arterial embolization as an innovative management strategy in a preterm neonatal case of complicated infantile hepatic haemangioendothelioma. (June 2019) - Watterson, Claire; Ferris, Kathryn; Molloy, Seana; Millar, David; Sweet, David
Abstract : Infantile hepatic haemangioendothelioma (IHH) is the commonest benign vascular tumour occurring in the first six-months of life. Medical treatment is first-line but a transcatheter arterial embolization (TAE) was also used in this preterm neonatal case; this is an innovative procedure used to reduce hepatic shunting by occluding the feeding vessels. Case report: A 2.09 kg male infant was delivered at 31 +3 weeks by emergency C-section. There were antenatal concerns regarding ascites and dilated bowel loops and at delivery he was noted to have hydrops. He required intubation and high frequency oscillatory ventilation. Extensive bruising and active bleeding from multiple sites was noted, so the massive blood transfusion protocol was initiated. An ejection systolic murmur was heard and he had hepatomegaly. Initial blood-work showed anaemia and disseminated intravascular coagulopathy. Thrombocytopenia was likely from Kasabach-Merritt syndrome (KMS). He also had deranged liver enzymes, jaundice and an acute kidney injury. AFP, thyroid function tests and urinary VMA were reassuring. Echocardiography demonstrated a small PDA and moderately impaired biventricular function. Abdominal ultrasound showed a mixed lesion involving both liver lobes, measuring 8.2×5.7 cm with dilated hepatic veins and ascites. MRI was not possible due to his unstable clinical condition. A large number of blood products were required including recombinant factor 7. Regular vitamin K and broad-spectrum antibiotics were initiated. Propranolol and dexamethasone were commenced to try to shrink the lesion. On day 3 of life he had embolization of his AVM, this was a novel procedure and involved accessing the coeliac axis via the umbilical artery and releasing micro-particles.Satisfactory devascularisation was achieved. Despite this innovative technique, he deteriorated secondary to high-output CCF, pulmonary oedema, anuria and hepatic failure.It was apparent to his parents and the multidisciplinary team that he would not survive and life-sustaining care was withdrawn on day 6. Discussion: It is clear that a multidisciplinary approach is required for the best treatment options. Corticosteroids (prednisolone) and propranolol are commonly prescribed and lesions unresponsive (15% cases) have been treated with antiangiogenic agents such as IFN-alpha, sirolimus, vincristine and cyclophosphamide.Invasive measures like hepatic artery ligation or embolization may be tried in complicated cases. Surgical therapy is recommended for uni-lobe lesions, masses with low potential for regression or in suspected malignancy. In summary, this case always had a poor prognosis as it was multifocal, had intra-hepatic shunting and was complicated by CCF and haemorrhage. Unfortunately TAE wasn't successful on this occasion but sub-speciality involvement was greatly appreciated.